cyclo{[(6-amino-6-deoxy-2,3 : 4,5-di-O-isopropylidene-D-galactonic acid)-( D-Phe)]2} - Bream, R; Watkin, D; Soengas, R; Fleet, G; Edwards, A; Hunter, S; Tranter, G (2006)
Determination of the crystal structure of the title compound [systematic name: 9,25-dibenzyl-4,4,15,15,20,20,31,31-octamethyl-3,5,14,16,19,21,30,32- octaoxa-8,11,24,27-tetraazapentacyclo[27.3.0.02,6.0 13,17.018,22]dotriacontane-7,10,23,26-tetrone], C 42H56N4O12, a cyclic tetramer, established the relative stereochemistry of its ten stereogenic C atoms; an interesting saddle-like conformation is adopted. There are two molecules in the asymmetric unit. With the exception of the phenyl and isopropylidene groups, the molecules are related by a non-crystallographic twofold rotation axis. There are varying degrees of disorder in the isopropylidene groups. © 2006 International Union of Crystallography. All rights reserved.